Factors affecting the benefit of the investment subjects of the Global Energy Internet - Wang, Bo; Zai, Wenjiao (IOP conference series. Materials Science and Engineering, 2018)
Investment decisions under Global Energy Internet(GEI) are characterized by complexity and diversity. The investment decisions under the GEI are influenced by resource system, market mechanism, economic technology, power investment environment and cooperation risk. In order to make better investment decisions, the following work is done in this paper. Firstly, the interaction between the electricity price system and the different income mechanism between different subjects is studied. Then, the relationship between the economic investment ability and the income of the market mechanism is analyzed. Finally, based on the foregoing research, the factors affecting the benefit of the investment subjects of the GEI are summarized.